(untitled) (Journal of the College of Basic Education, 2022)
The study aimed to know the relationship between professional satisfaction and some demographic variables among teachers (gender, years of service, academic qualification). The results of the study revealed the prevalence of occupational satisfaction in the research sample, and the prevalence of each dimension of the occupational satisfaction scale was medium. The current research also showed that the percentage of satisfaction with self-realization of the profession appeared in a moderate degree according to some demographic variables. As well as the percentage of satisfaction with the nature of work and the relationship with officials